Inflammatory and bone turnover markers in a cross‐sectional and prospective study of acute Charcot osteoarthropathy. Issue 2 (17th October 2014) - Petrova, N. L.; Dew, T. K.; Musto, R. L.; Sherwood, R. A.; Bates, M.; Moniz, C. F.; Edmonds, M. E.
Abstract Aims To assess markers of inflammation and bone turnover at presentation and at resolution of Charcot osteoarthropathy. Methods We measured serum inflammatory and bone turnover markers in a cross‐sectional study of 35 people with Charcot osteoarthropathy, together with 34 people with diabetes and 12 people without diabetes. In addition, a prospective study of the subjects with Charcot osteoarthropathy was conducted until clinical resolution. Results At presentation, C‐reactive protein (P = 0.007), tumour necrosis factor‐α (P = 0.010) and interleukin‐6 (P = 0.002), but not interleukin‐1β, (P = 0.254) were significantly higher in people with Charcot osteoarthropathy than in people with and without diabetes. Serum C‐terminal telopeptide (P = 0.004), bone alkaline phosphatase (P = 0.006) and osteoprotegerin (P < 0.001), but not tartrate‐resistant acid phosphatase (P = 0.126) and soluble receptor activator of nuclear factor‐κβ ligand (P = 0.915), were significantly higher in people with Charcot osteoarthropathy than in people with and without diabetes. At follow‐up it was found that tumour necrosis factor‐α (P = 0.012) and interleukin‐6 (P = 0.003), but not C‐reactive protein (P = 0.101), interleukin‐1β (P = 0.457), C‐terminal telopeptide (P = 0.743), bone alkaline phosphatase (P = 0.193), tartrate‐resistant acid phosphatase (P = 0.856), osteoprotegerin (P = 0.372) or soluble receptor activator of nuclear factor‐kβ ligand (P = 0.889), had significantly decreased between presentation and the 3 months of casting therapy time point, and all analytes remained unchanged from 3 months of casting therapy until resolution. In people with Charcot osteoarthropathy, there was a positive correlation between interleukin‐6 and C‐terminal telopeptide (P = 0.028) and tumour necrosis factor‐α and C‐terminal telopeptide (P = 0.013) only at presentation. Conclusions At the onset of acute Charcot foot, serum concentrations of tumour necrosis factor‐α and interleukin‐6 were elevated; however, there was a significant reduction in these markers at resolution and these markers may be useful in the assessment of disease activity.